2020
DOI: 10.3390/mi11050469
|View full text |Cite
|
Sign up to set email alerts
|

Milling Microchannels in Monel 400 Alloy by Wire EDM: An Experimental Analysis

Abstract: This paper presents the results of an investigation on the capacity of wire electrical discharge machining (WEDM) to produce microchannels in the Nickel-based alloy, Monel 400. The main objective of the current study is to produce microchannels with desired/target geometry and acceptable surface quality. Square cross-sectional microchannels with dimensions of 500 × 500 µm were investigated. Experiments were conducted based on the one-factor-at-a-time approach for the key input WEDM process parameters, namely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The results showed that increasing the current (from 2A to 12A) reduced the cutting time (by 60.95%) while keeping all other parameters constant. Likewise, in similar studies [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] related to the WIRE-EDM of PCMs, it was observed that the quality and accuracy of holes in a low-conductive material can be regulated by applying a conductive layer above the non-conductive PCM. Also, the development of theoretical models of the WIRE-EDM of PCMs provides a guide to obtain the accuracy required in the process [37].…”
Section: Introductionmentioning
confidence: 83%
“…The results showed that increasing the current (from 2A to 12A) reduced the cutting time (by 60.95%) while keeping all other parameters constant. Likewise, in similar studies [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] related to the WIRE-EDM of PCMs, it was observed that the quality and accuracy of holes in a low-conductive material can be regulated by applying a conductive layer above the non-conductive PCM. Also, the development of theoretical models of the WIRE-EDM of PCMs provides a guide to obtain the accuracy required in the process [37].…”
Section: Introductionmentioning
confidence: 83%
“…A similar character is seen in Figure 11 for 2024 (D16) duralumin. The studies [2,11,[15][16][17]19,[46][47][48] show that penetration (adsorption in the recast layer) of the tool electrode material components can reach a depth of 10 µm (from 2.55 up to 50 µm depending on used materials of electrodes, dielectric medium, and experiment factors). At the same time, this uneven distribution of the workpiece and wire elements can be explained by sublimation phenomena of the recast layers (similar to laser ablation during heating with the concentrated energy flows such as laser, plasma, electric discharges, fast energy neutral atoms [49][50][51][52]), when components of workpiece material sublimate primarily [53,54].…”
Section: Submicrostructure Of Surface and Subsurface Layersmentioning
confidence: 99%
“…Wire electrical discharge machining of Ni-Cu alloy (67% Ni-23% Cu, Monel 400) showed the formed recast layer of 2.55 µm [17]. The surface layer's microhardness was 172-220 HV and increased steadily up to the depth of 20 µm up to 260-275 HV values.…”
mentioning
confidence: 99%
“…For example, Ahmed et al [ 5 ] conducted the experiment on the manufacture of high-aspect-ratio thin structures of micrometer thickness (117–500 μm) from D2 steel through WEDM. In order to produce microchannels with desired/target geometry and acceptable surface quality, Saleh et al [ 6 ] carried out the results of an investigation on the capacity of WEDM to produce microchannels in the nickel-based alloy, Monel 400. WEDM is one of typical kind of EDM, they are developed by using the phenomenon of spark erosion, and a lot of research has been carried out in various aspects relating to improving performance measures, optimizing the process variables, and monitoring and controlling the sparking process [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%